Родовий відмінок однини іменників жіночого роду в західнополіських і суміжних говірках - Зінчук, Руслана Степанівна; Zinchuk, R. S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
На матеріалі західнополіських і суміжних говірок проаналізовано флексійну систему родового відмінка однини іменників жіночого роду, встановлено високий ступінь варіантності відмінкових формантів, з’ясовано чинники впливу на існування діалектних відмінностей у досліджуваній відмінковій позиції. The article is devoted to the analysis of the genitive case inflectional system of feminine singular nouns in Western Polissian and their contiguous dialects. The formation of genitive case of feminine singular nouns is analyzed as one of the typical representative of the variation of case endings in a particular position on the basis of Western Polissian and their contiguous dialects. The factors of the influence on the existence of dialectal differences in the represented inflection system are observed. A high degree of variability of case formants nouns, which are designed on the basis of model of ancient *-ā- and *-jā-bases, are found to define consequences of typical phonetic patterns for this areal and analogous processes. Versions on options on -и and -′(’) і are represented as an interaction between ancient and modern expressions in the analyzed case position of substantives, which are organized on the basis of *-ǐ-bases. Typically Western Polissian phonetic-morphological neologism – matera, form of genitive singular noun of ancient consonantal type on *-r- is noted.
The Inflection System of Genitive Case of Feminine Singular Nouns in Western Polissian and Their Contiguous Dialects
Keywords: говірка; словозміна; іменник; словоформа; флексія; граматична аналогія; фонетична інновація; dialect; inflection; noun; word form; flexion; grammatical analogy; phonetic innovation